2012
DOI: 10.1159/000339441
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Marfan Syndrome and Related Connective Tissue Disorders: An Update 2012

Abstract: Marfan syndrome (MFS) is an autosomal dominant disorder of the connective tissue characterized by early development of thoracic aortic aneurysms/dissections together with symptoms of the ocular and skeletal systems. While most patients/families with a classic phenotypic expression of MFS harbour mutations in the gene encoding fibrillin-1 (FBN1), genetic studies of the recent years revealed that the clinical features, as well as the mutated genes, show a high degree of overlap between MFS and other connective t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 141 publications
1
36
0
1
Order By: Relevance
“…AD usually occurs in non-syndromic and sporadic form (~80%) or in association with hereditary genetic disorders, such as familial thoracic aortic dissection (fTAAD), Marfan syndrome (MFS), the vascular type of Ehlers-Danlos syndrome (EDS), Loeys-Dietz syndrome (LDS), and arterial tortuosity syndrome (ATS) (Goldfinger et al, 2014;Hoffjan, 2012;Khau Van Kien et al, 2004;Ritelli et al, 2009). Although previous genetic studies in familial AD cases have identified several genes (Table S1 in Supporting Information) responsible for this disease, large fraction of clinical cases, especially sporadic cases, still lack genetic targets (Campens et al, 2015;Guo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…AD usually occurs in non-syndromic and sporadic form (~80%) or in association with hereditary genetic disorders, such as familial thoracic aortic dissection (fTAAD), Marfan syndrome (MFS), the vascular type of Ehlers-Danlos syndrome (EDS), Loeys-Dietz syndrome (LDS), and arterial tortuosity syndrome (ATS) (Goldfinger et al, 2014;Hoffjan, 2012;Khau Van Kien et al, 2004;Ritelli et al, 2009). Although previous genetic studies in familial AD cases have identified several genes (Table S1 in Supporting Information) responsible for this disease, large fraction of clinical cases, especially sporadic cases, still lack genetic targets (Campens et al, 2015;Guo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Since many patients carrying FBN1 mutations may develop classic MFS over time, genotype information is essential for the diagnosis or exclusion of MFS [Sheikhzadeh et al, 2012], despite the fact that knowledge about a specific FBN1 mutation seems to have little prognostic value for an individual patient and cannot reliably guide individual management [Hoffjan, 2012]. In our case, although the FBN1 C538P mutation seems not to favor the progression of aortic root dilatation, periodic echocardiograms should be performed to prevent the risk of aortic dissection in the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis of a tall, young person with Marfan-like skeletal features includes homocystinuria, Stickler syndrome, Ehlers-Danlos syndrome (EDS), Loeys-Dietz syndrome (LDS) and MASS phenotype (the acronym represents the following manifestations: a prolapsed mitral valve, myopia, aortic root enlargement, and skeletal and skin manifestations) [6,12,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, approximately one-fourth of MFS cases are caused by de-novo mutations. It has been demonstrated that fibrillin-1 microfibrils participate in the regulation of transforming growth factor β (TGF-β) [5,6]. Normally, in a healthy individual TGF-β is bound to connective tissue by fibrillin-1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation